A novel reagent for spectroscopic determination of Mo(VI) - KAKI, ESRA HACER (VERSITA, 2012)
A new reagent for spectrophotometric determination of Mo(VI) was developed utilizing micellar effects. For this purpose, differences in the ultraviolet and visible spectral properties of Mo(VI), gallic acid, L-serine, and their binary and ternary solutions were studied in the presence and absence of cationic, anionic, and non-ionic surface active agents. L-serine was observed to form binary complexes and a ternary complex with Mo(VI) and gallic acid below its isoelectric point. The maximum Mo(VI) sensitivity was exerted by the Mo(VI) + gallic acid + L-serine + hexadecyltrimethylammonium bromide system at pH of 4.5. This system was proposed for use in the spectrophotometric determination of Mo(VI) as a superior alternative to the Mo(VI) + gallic acid + hexadecyltrimethylammonium bromide system and to most of the instrumental analysis methods referred to in the literature. The mechanism of micellar effects was discussed on the basis of the spectral data obtained above and below the isoelectric point of L-serine and explained in terms of the molecular charge of the substrates and the surfactants. (C) 2011 Institute of Chemistry, Slovak Academy of Sciences
Keywords: molybdenum(VI); gallic acid; L-serine; complexation; micellar effects; hexadecyltrimethylammonium bromide; TRACE AMOUNTS; SPECTROPHOTOMETRIC DETERMINATION; PROTONATION EQUILIBRIA; BROMOPYROGALLOL RED; MICELLAR MEDIA; MOLYBDENUM; SAMPLES; WATER; ACID; PRECONCENTRATION